1987
DOI: 10.1039/c39870001070
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of the solid state structures of bisparaphenylene-(3n+ 4)-crown-n ethers upon macrocyclic ring size

Abstract: X-Ray crystallography on the free BPP(3n+4)Cn ethers where n = 7, 8, 10, 11, and 12 reveals a conformational dependence for the macrocycles which is reflected in their cavity sizes, with a maximum for n = 10, and in the relative orientations of the two hydroquinol rings, almost orthogonal for n = 7 and parallel or nearly parallel for n = 8, 10, 11, and 12, with respect to each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…In compounds 11 and 12 , the overlap of the aromatic systems is immediately apparent, being approximately the same in the both molecules (Figure 3, left column). A similar molecular shape has been found in the macrocycles that incorporate hydroquinol,12 or biphenyl units bridged by the oxyethylene chains of the same length,13 while in the case of the anthracene backbone the elongated shape of the molecule is distorted 14. In compound 13 , the parallel arrangement of the fluorenone units is retained; however, one of them is considerably displaced with respect to the other in order to optimize the dipole–dipole interactions between the carbonyl groups.…”
Section: Resultssupporting
confidence: 55%
“…In compounds 11 and 12 , the overlap of the aromatic systems is immediately apparent, being approximately the same in the both molecules (Figure 3, left column). A similar molecular shape has been found in the macrocycles that incorporate hydroquinol,12 or biphenyl units bridged by the oxyethylene chains of the same length,13 while in the case of the anthracene backbone the elongated shape of the molecule is distorted 14. In compound 13 , the parallel arrangement of the fluorenone units is retained; however, one of them is considerably displaced with respect to the other in order to optimize the dipole–dipole interactions between the carbonyl groups.…”
Section: Resultssupporting
confidence: 55%
“…This type of noncovalent weak interaction resulted in a large spectral redshift in most cases. It is normal for weak interactions such as aromatic CH/π interactions to exist in some simple cyclophane systems 17–21. We observed that the effect of the transannular π–π interaction on the optical properties varied with the rigidity of the polymer backbone 16.…”
Section: Introductionmentioning
confidence: 84%
“…It is normal for weak interactions such as aromatic CÀ ÀH/p interactions to exist in some simple cyclophane systems. [17][18][19][20][21] We observed that the effect of the transannular p-p interaction on the optical properties varied with the rigidity of the polymer backbone. 16 Here we report two types of bipyridinophane-based conjugated polymers that include an intramolecular aromatic CÀ ÀH/p interaction system.…”
Section: Introductionmentioning
confidence: 99%
“…6), the four-carbon chain linkers permit an intramolecular stacking interaction, similar to that observed in macrocyclic systems such as bis(1,4-phenylene)crown ethers with ether chain linkers of appropriate length. 11 The interplanar separation is 3.44 Å and the benzene centroid-tocentroid distance is 3.91 Å. Clearly, this precludes the existence of any cavity within the macrocycle, and this interaction is likely to persist in solution.…”
Section: X-ray Crystal Stucturesmentioning
confidence: 99%